Using a television programme as a tool to increase perceived awareness of mental health and well-being – findings from 'Our Mental Health' survey. (4th March 2023) - McTernan, N.; Ryan, F.; Williamson, E.; Chambers, D.; Arensman, E.
Abstract : Background: International research shows that media can increase knowledge, raise public awareness and reduce stigma relating to mental health. Methods: Following the broadcast of a documentary on national television featuring interviews with young people who had experienced mental health difficulties and suicidal behaviour, an anonymous online survey, aimed at examining public perceptions of the impact of a television documentary, was conducted, using a mixed methods approach. Results: 2311 people completed the survey. Of those who watched the documentary and answered the closed questions ( n = 854), 94% stated that the documentary will positively impact young people's mental health and well-being. The majority (91%) stated that the documentary will encourage young people to talk to someone if experiencing difficulties and 87% indicated it will help to reduce stigma associated with mental health. Viewers had a 5% higher level of intention to seek help than non-viewers. Participants indicated that the identifiable personal stories and discourse around stigma and shame, and the increased understanding and awareness gained, had the most profound impact on them. Conclusions: These findings indicate that a documentary addressing mental health and suicidal behaviour, which incorporates real life identifiable stories of resilience and recovery, has the potential to impact positively on emotional well-being and general mood, to reduce stigma related to mental health and to encourage help-seeking behaviour. Documentaries including these concepts, with a public mental health focus and a consistent message, incorporating pre- and post-evaluations, and customisation for target audiences in compliance with current media recommendations, should be considered.